Public Relation Detachment of Community Schools: A Study of Duduwa Rural Municipality, Banke, Nepal. - Pokharel, Bishnu Prasad (Journal of Development Review, 2023)
A strong bond between school family and community should be indispensable. Students severely suffer when they fail to maintain mutual respect between these two stakeholders. The research suggests a viable solution after unfolding the existing detachment of the secondary level community schools with the social accessory in Duduwa Municipality of Banke district in the western part of Lumbini Province, Nepal. I purposively selected the secondary  schools of Duduwa Rural Muncipality to explore the problematic in relationship with society and the school family. The rationale behind the selection lies in the low academic achievement of the students. I used observation, interview, and document review to collect the information from the selected schools. The school teachers and guardians have a grudge against the lack of proper educational value and quality upgrading education. The academic discussion got the inference that imagined dominant knowledge of the head teacher, members of the school management committee, president of parent teachers’ association and teachers detaches relation with the society. Therefore, the research recommends measures to be taken by the school management committee and the school family to develop smooth and healthy relations with the public to improve public involvement in quality accreditation.